Spatial Sustainability as A Contextual Tool to Code Emerging Urban Patterns of Cities - Aparna Rajeevan; Saritha G Parambath; Bejene S Kothari (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
As cities grow, the urban system expands and the contribution of each architect or urban designer into the system is different. Every increment is unique in its own character and expresses the attitude of the designer through it. Hence any increment into the system should be a continuation of what was existing before and should give due values to the existing condition without which the system tends to break. Doing so can lead to formation of a spatially sustainable fabric or city but to attain this kind of sustainability, every type of fabrics in every cities should follow a set of codes which are unique to themselves because spatial sustainability depends upon the spatial and social organization of spaces, geometric and configurational ordering of the space, culture and way of life in a city. Space syntax and spatial cognition were the methods used to identify parameters that contribute to spatial sustainability.